PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAME TOURNAMENT) UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS XI MIPA 1 SMA NEGERI 10 MATARAM PADA MATA PELAJARAN BIOLOGI TAHUN AJARAN 2022/2023 - Fitri Rahmayanti; Nur Aini; Khaeruddin Khaeruddin (JURNAL ASIMILASI PENDIDIKAN, 2023)
Education is one of the essential aspects included in the preamble of the Indonesian Constitution. Education is closely related to the teaching and learning activities. Learning is an activity often considered very boring by students. The low learning interest, especially in the Science subjects, has a negative impact on students' learning outcomes. Biology, as one of the branches of science, is often seen as a subject with dense and dull theories. This issue is exacerbated by the teaching style of teachers, which tends to be teacher-centered. This research is a Classroom Action Research (CAR) designed with the implementation of the Team Games Tournament (TGT) cooperative learning model based on Lesson Study. The stages involved in this research include the planning, implementation, and observation stages conducted over two cycles. The research was carried out at SMA Negeri 10 Mataram, specifically in class XI MIPA 1, with a sample size of 30 students. The objective of this research is to increase students' interest in learning Biology by applying the TGT cooperative learning model. The data analysis technique in this research uses qualitative descriptive methods. The results of the research indicate that the application of the TGT cooperative learning model can increase students' learing interest by 66.67% with a "satisfactory" category.